Childhood asthma and chronic obstructive pulmonary disease. Issue 2 (April 2015) - Tai, Andrew
<x xml:space="preserve">Abstract</x> Purpose of review There has been recent interest in understanding the origins of chronic obstructive pulmonary disease. Epidemiological studies suggest that chronic obstructive pulmonary disease clearly has other causes apart from tobacco smoke. Recent findings Cross-sectional studies of adult cohorts with chronic obstructive pulmonary disease highlight that childhood asthma is a risk factor. A recent longitudinal childhood cohort study of children from childhood to the age of 50 years describes that children with severe asthma are at increased risk of chronic obstructive pulmonary disease and that the deficit in lung function can be tracked back to early years. Summary Children with severe asthma are at increased risk of developing chronic obstructive pulmonary disease.